Scooby-Doo! - Calvo, Emily Thorton (Lincolnwood, Ill. : Publications International, 1999)
Search for the Scooby-Doo in this book of detailed drawings.
Keywords: Scooby-Doo (Fictitious character) -- Fiction; Picture puzzles; Literary recreations